Association between vaginal microecological alterations and high-risk human papillomavirus infection: a cross-sectional study - Peng, Nanqiu; Xiao, Jing; He, Li; Xie, Li (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveThis study aimed to investigate the correlation between alterations in the vaginal microecological environment and high-risk human papillomavirus (HR-HPV) infection, thereby providing a theoretical basis for clinical prevention and early intervention.MethodsA total of 854 patients who visited the gynecology outpatient clinic at Wusong Central Hospital, Baoshan District, Shanghai, between June and December 2023 were included. Vaginal secretions were collected for HPV genotyping and microecological analysis. Patients were categorized into HR-HPV-positive (n=222) and HR-HPV-negative (n=632) groups. The detection rates of various HR-HPV subtypes (HPV 16, 18, 31, 33, 35, 39, 45, 51, 52, 53, 56, 58, 59, 66, 68, 73, 82) were analyzed. Key microecological indicators—including vaginal pH, hydrogen peroxide, leukocyte esterase, sialidase, Lactobacillus levels, and vaginal cleanliness—were compared between the two groups, and their predictive value for HR-HPV infection was assessed using ROC curve analysis.ResultsSignificant differences were observed between the two groups in terms of vaginal pH, hydrogen peroxide, leukocyte esterase, sialidase activity, Lactobacillus abundance, and vaginal cleanliness (all P < 0.05). The ROC curve analysis yielded an AUC of 0.701, indicating moderate predictive value.ConclusionChanges in the vaginal microecological environment are significantly associated with HR-HPV infection. Monitoring vaginal microecological indicators may provide adjunctive information for clinical prevention and early intervention, though further prospective studies are needed to establish causality.